Hubungan Pengetahuan dan Kepatuhan Perawat dengan Penerapan Budaya Keselamatan Pasien - Inas Syabanasyah; Solehudin Solehudin (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
The implementation of patient safety culture in hospitals is often faced with a number of problems that can affect its effectiveness. The aim of this research is to determine the relationship between knowledge and care compliance with the implementation of patient safety culture. The research uses a correlational analytical method with a cross sectional approach. Statistical analysis uses multiple linear regression. The population in this study was 310 inpatient nurses from private hospitals in Jakarta. The sampling formula uses Slovin, the sample size is 175 people. The research results show that simultaneously and partially knowledge and compliance are significantly related to the implementation of patient safety culture with a p value of 0.001. Implement training programs that focus on increasing medical personnel's knowledge regarding patient safety practices. Ensure that training includes an in-depth understanding of the risks and required safety protocols.